Penegakan Hukum Lingkungan Terhadap Masyarakat Adat Yang Melakukan Eksploitasi Di Wilayah Pesisir - Wattimena, Ricky Marthen (Balobe Law Journal, 2024)
Introduction: Environmental law enforcement is one of the processes carried out to provide legal certainty. In principle, indigenous peoples always carry out exploitation in coastal areas, so law enforcement is needed so that it can run optimally, where this experiences obstacles in the process and causes environmental law enforcement to not run effectively.Purposes of the Research: To find out the enforcement of environmental law against indigenous communities who exploit coastal areas and the obstacles in enforcing environmental law for indigenous communities in coastal areas.Methods of the Research: The method used in this study is normative- juridical, which focuses on the main law by examining theories, concepts, legal principles, and laws and regulations related to this research.Results of the Research: Environmental law enforcement can run well through criminal, administrative and civil aspects. Enforcing environmental laws for indigenous communities against exploitation in coastal areas has become very difficult. This is influenced by legal factors, law enforcement, facilities and infrastructure, society and culture itself. These five factors are one of the things that causes environmental law enforcement to not run optimally. For this reason, there must be cooperation between regional governments and law enforcement in order to prevent prolonged exploitation and cause marine areas to become damaged and not well controlled, so that regional governments must coordinate with stakeholders in the regions, in this case the environmental services and village governments. locally to follow up on problems in coastal areas resulting from sand and coral mining by indigenous communities.